‘Look for the right mentor’: an interview with Prof. Manfred V. Singer - Fernandez-Zapico, Martin E. (Pancreatology, 2007)
Prof. Manfred V. Singer, a pioneer in the field of neuro-hormonal regulation of pancreatic exocrine secretion, is interviewed. He provided the first experimental proof of the existence of neural reflexes that control pancreatic functions. Here, Prof. Singer shares his life experience in pancreatic research and points out key aspects of a successful mentormentee relationship.
Gesehen am 27.04.2022